Pricing Strategies Evaluation in Radio Industry’s Firm (Case Study at PT XYZ) - Halimatussakdiah Halimatussakdiah; Rafika Yuniasih (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2020)
The purpose of this research is to analyze the pricing strategy and product prices that can be applied by PT XYZ. The method used is qualitative research. The study concluded that the pricing strategy that should be applied by PT XYZ is value-based pricing strategy. By using value-based pricing, the company will have a better understand of client’s current conditions, and can fulfill client requests depending on their budget for promotion. In addition, by using value-based pricing properly, will result in increase consumer loyalty increase to the company. The minimum price that PT XYZ can offer for spot products is Rp 44,221 and Rp 27,507 for adlibs products. PT XYZ can also provide advertising packages that can match according to the client’s budget, starting from IDR 1,000,000.